Mainstreaming the Use of Remote Sensing Data and Applications in Operational Contexts - World Bank Group (World Bank, Washington, DC, 2018)
This report presents the activities and outcomes to date of the global initiative on remote sensing for water resources management phase two. The Initiative was conceived to help mainstream the use of beneficial remote sensing applications in operational projects of the Bank, as well as to facilitate the adoption of remote sensing applications in World Bank client countries. By bridging the gap between the supply of remote sensing data and the needs from the Bank’s operational projects, Earth Observations can better inform client country agencies by improving monitoring and predictive capabilities and supporting better water-related operations. This report is addressed to technical staff in national water agencies, project leads from development and financing institutions, and water practitioners in general. The goal of the report is to present insights from a range of innovative remote sensing applications developed within the Remote Sensing Initiative, to help address specific water resources management challenges. The results presented here include constraints identified in the adoption of remote sensing, the approaches adopted to make applications functional in different contexts, the project applications themselves, insights on their sustainability, and ways forward. These applications can be replicated, up-scaled, and adapted in many other contexts to address similar challenges. We hope the information contained in this report will help country agencies and project teams in integrating the use of remote sensing in their water resources management practices, as well as in project design, implementation, monitoring and evaluation.